Validation of Physiological Strain Index Based on Heart Rate in Experimental Hot Conditions - Ayoub Ghanbary Sartang; Habibollah Dehghan (Iranian Journal of Health, Safety and Environment, 2016)
Heat stress is a common problem in industrial workplaces. Thermal stress is a caused reduces concentration of and fatigue increases individuals and thermal condition can be one of accident risk factors .The purpose of this study was validation of Physiological Strain Index Based on Heart Rate in experimental condition. This Semi experimental study was conducted to 16 male in five different temperature conditions (21, 24,27,30,35ºC) in the climate chamber and on the treadmill with two levels of activity 2.4 kph (light physical activity) and 4.8 kph (medium physical activity).Heart rate was measured to for calculating Physiological Strain Index Based on Heart Rate, rate perceived exertion and questionnaire Heat Strain Score index was measured. The correlations between the indices were evaluated using Pearson correlation test and regression analysis. Pearson correlation test showed a significant correlation between Physiological Strain Index Based on Heart Rate and rate perceived exertion (p≤0.001,r=0.96).also a high correlation was observed between Physiological Strain Index Based on Heart Rate and wet bulb globe temperature (p≤0.001,r=0.90). A very high correlation was observed between Physiological Strain Index Based on Heart Rate and Heat Strain Score Index (p≤0.001, r=0.93). The results of this study showed Physiological Strain Index Based on Heart Rate a suitable method for strain heart evaluation is caused by thermal stress because there was an acceptable correlation with heat stress valid indices.